HUKUM KREDIT KEPEMILIKAN RUMAH (KPR) DALAM PERSPEKTIF ISLAM - Apriyanti, Ira (UI Scholars Hub, 2020)
Home is one of the primary needs that must be reached. The importance of sufficing these needs causes the demand for homes is increasing every year. Compared to 2018, the growth of Home Ownership Loans (KPR) in January 2019 increased by 147 basis points (bps) from the original 10.89% to 12.36%. It is estimated that credit growth is expected to increase in line with optimism about the strengthening monetary and economic conditions, supported by the risk of lending that is relatively well maintained. But to fulfilling these needs, not every person can easily buy a house in cash. As a result, many banks offer a variety of options to bridge the fulfilment of society needs for housing with the developer by applying the principle of credit in conducting transactions. In this conventional transaction, a loan agreement is accompanied by interest that continues to increase every year. Accordingly this paper will review the House Ownership Credit law by conventional banks based on Islamic law.